Research on the sedimentary characteristics of organic matter in lacustrine mudrocks and their hydrocarbon generation potential based on palynofacies analysis: Eocene shahejie formation, dongying sag - Zeng, Xiang; Cai, Jingong; Wang, Xuejun; Zhang, Xuejun; Yan, Jianping; Zhu, Weilin; Dong, Zhe; Bian, Lizeng (Frontiers in Earth Science, 2022)
Lacustrine mudrocks are important hydrocarbon source rocks due to their high contents of organic matter (OM). An accurate determination of the origins of OM in the rocks can contribute greatly to the identification of the sedimentary environment and the evaluation of the hydrocarbon generation capacity of the mudrocks. In this study, the lacustrine mudrocks of the Eocene Shahejie Formation in the Dongying Sag of China were sampled for further discussion of the types and origins of OM and the hydrocarbon generation capacity of the mudrocks. On that basis, the classical palynofacies classification scheme was improved, and five palynofacies types (PF1 to PF5) were classified to accurately reflect different lacustrine environments. Among them, PF1 to PF3 are rich in various amorphous organic matter (AOM), including benthic microbial mats, organic aggregates and algal aggregates, which are part of the lake environment in which aquatic organisms bloom. The hydrocarbon generation abilities of the three palynofacies are different but generally strong. PF5 and PF4 have abundant terrestrial plant fragments and macrophyte fragments, respectively, indicating a shallow, near-provenance lake environment and a shallow, macrophyte-flourishing lake environment. These two types of palynofacies have weaker hydrocarbon generation capacities than the former three. Due to the enrichment of different types of palynofacies, each formation of the Dongying Sag shows distinct hydrocarbon generation potentials. Therefore, it is important to pay special attention to the origin of OM and its influences on the hydrocarbon generation capacity of lacustrine mudrocks for a better understanding of the deposition and hydrocarbon generation potential of source rocks.